Supply Chain Performance Measurement at Batik Industry MTO Type Using SCOR 12.0 and AHP - Syarif Hidayatuloh; Nabila Noor Qisthani (School of Industrial and System Engineering, Telkom University, 2020)
Batik Kraton SME is one of the industries in Pekalongan that has been producing batik for 20 years. TheSME has never conducted supply chain measurements before, even though the industry has been aroundfor a long time. Quick-change in customer behavior become the obstacle for the industry. Supply chainperformance measurement will be carried out to determine whether the industry is superior or not inmanaging their supply chain and what improvements must be conducted in order to compete in the market.Performance measurement will involve supply chain processes and indicator metrics. The methods used inthis research are SCOR 12.0 Model and Analytical Hierarchy Process which for make to order type ofproduction process. The results of the supply chain performance measurement show an average score of69.39 which is included in the average or medium category. Each performance score of the core processesfor plan, source, make, deliver, return, and enable are 87.05; 94.25; 68.13; 79.79; 75.47; 11.66. It isacknowledged that the highest score of process performance is “source” and the lowest score is “enable”.These indicators inform that the supply chain process at Batik Kraton SME still needs improvement inseveral sectors.